FEATURES RECONSTRUCTION OF THE HISTORICAL DEVELOPMENT AND ENVIRONMENTAL REGULATION (Municipal economy of cities (Technical science), 2013)
We investigate the specificity of the ecological reconstruction in the historic city center. Identify methods of optimization of the architectural environment of human life in different ways